2014
DOI: 10.1111/nph.13065
|View full text |Cite
|
Sign up to set email alerts
|

Biological control of invasive plant species: a reassessment for theAnthropocene

Abstract: Contents 490I.490II.491III.492IV.494V.497VI.498499References499 Summary The science of finding, testing and releasing herbivores and pathogens to control invasive plant species has achieved a level of maturity and success that argues for continued and expanded use of this program. The practice, however, remains unpopular with some conservationists, invasion biologists, and stakeholders. The ecological and economic benefits of controlling densities of problematic plant species using biological control agent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(67 citation statements)
references
References 148 publications
0
63
0
2
Order By: Relevance
“…Also, we did not find higher growth rates in the native species. Possibly, the presumed advantage of native species due to their adaptations for resprouting after fires was compensated by the equally good advantage of non-native species gained at their new range by having less or no specific predators, less competition, or having a climate better suited to the species than the climate at the native range (Mack et al 2000;Seastedt 2014). Supporting this explanation studies in the Chaco Serrano of the functional traits of non-native tree species have shown higher growth rates than native tree species Zeballos et al 2014).…”
Section: Post-fire Growth Of Resproutsmentioning
confidence: 99%
“…Also, we did not find higher growth rates in the native species. Possibly, the presumed advantage of native species due to their adaptations for resprouting after fires was compensated by the equally good advantage of non-native species gained at their new range by having less or no specific predators, less competition, or having a climate better suited to the species than the climate at the native range (Mack et al 2000;Seastedt 2014). Supporting this explanation studies in the Chaco Serrano of the functional traits of non-native tree species have shown higher growth rates than native tree species Zeballos et al 2014).…”
Section: Post-fire Growth Of Resproutsmentioning
confidence: 99%
“…Plants assigned to the Ophraella treatment received a centrifuge tube near their stem before the tissue was closed, and which contained six male beetles and three unhatched egg batches each containing a minimum of 10 eggs on pieces of leaves, natural enemies from the native range are introduced to control the plant in the invaded range (Müller-Schärer & Schaffner 2008). This method has proven to be permanent, environmentally friendly and a cost-effective control of several invasive plants (Seastedt 2015). In 2013, the leaf beetle Ophraella communa LaSage (Coleoptera: Chrysomelidae), already used as a biocontrol agent of ragweed in China (Zhou et al 2011) and also effective against ragweed in Australia (Palmer et al 2010), was unexpectedly found to have established in Northwestern Italy and southern Switzerland (Boriani et al 2013;Müller-Schärer et al 2014).…”
Section: Methodsmentioning
confidence: 99%
“…As the human-mediated biogeographic processes that characterize the Anthropocene continue to intensify, there is a growing recognition of wicked problems in conservation management around the world (Game et al 2014, Seastedt 2014. As anthropogenic dispersal of organisms continues to grow and conservation budgets remain constrained in a volatile global economy, the management of invasive species will increasingly require novel approaches, including heuristic assessments of the ecological risk associated with proposed interventions, and adaptive, stakeholder-conscious management through structured engagement initiatives, to enable positive outcomes for ecosystem integrity.…”
Section: Yesmentioning
confidence: 99%
“…The term was used by Evans et al (2008), citing difficulties encountered when managing aquatic pests in the Crystal River, Florida; by McNeely (2013) when describing the management of plant introductions in conservation areas; and by Seastedt (2014) when describing the socio-political and ethical issues surrounding biocontrol. The management of biological invasions is particularly susceptible to wickedness in the form of conflicting social pressures.…”
Section: Introductionmentioning
confidence: 99%